(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Acquired immunodeficiency in pediatric populations demonstrates distinct alterations in peripheral blood cellular composition and immunophenotypic profiles. This investigation examined hematological and immunological parameters in 87 children aged 3 to 14 years with documented secondary immunodeficiency. Flow cytometric analysis revealed significant reductions in CD4+ lymphocyte populations and altered CD4/CD8 ratios compared to age-matched controls. Quantitative immunoglobulin assessments demonstrated variable patterns correlating with infection frequency. These findings establish specific immunomorphological markers that may facilitate early detection and monitoring of immunodeficient states in pediatric practice.